OC-047 A multi disciplinary team (mdt) approach for complex benign colo rectal polyps: a tertiary referral centre experience. (22nd June 2015) - Tsiamoulos, Z; Rameshshanker, R; Wawszczak, A; Elliott, T; Beintaris, I; Bourikas, L; Garg, M; Rajendran, A; Spranger, H; Peake, S; Patel, K; Thomas-Gibson, S; et al.
Abstract : Introduction: Multi-disciplinary team (MDT) working is an established part of cancer care. Limited data is available on their impact for benign complex colorectal polyps. Increased numbers of these polyps are referred to our tertiary centre for further management. Method: Polyp MDT comprising of gastroenterologists, colorectal surgeons and histopathologists was established in January 2013 to discuss the management of complex polyps (large or recurrent polyps or those where endoscopic access was difficult). Cases that were referred to individual consultants and had a provisional management plan made were then discussed at the MDT and a consensus management plan was agreed. The impact of MDT management plan was then evaluated. Results: 96 cases were discussed between January 2013 and October 2014. Of those 75 (78%) were tertiary referrals. The reasons for polyp complexity included large polyps 53 (55%), those with difficult access 52 (54%) and previous failed attempt 35 (36%). Majority of the polyps were in recto sigmoid, 49 (51%) or in caecum, 32 (32%). In 38 cases (40%) provisional management plan was changed after MDT discussion. This plan was then followed in 80/96 (82%) cases. Combined surgical-endoscopic approaches were proposed in 68 cases (65%). 25/96 patients had polypectomy during a single hospital visit. The remaining cases (71/96) needed further assessment before attempted polypectomy. Complete polypectomy was achieved in 85/96 (89%) of patients: endoscopically in 75/96 cases (78%): 38 by endoscopic excision alone and 37 by combined endo-surgical approaches. Ten polyps were resected surgically. Of the remaining 11 patients no polyps were found in 2 of those referred, 2 patients were referred back their local hospital for surgery, 5 were not fit for a polypectomy and are under surveillance, 1 had metastatic colorectal cancer and 1 declined any intervention. Cancer was found in 7/96 polyps and 6/7 had surgical resection (the remaining patient had metastatic disease). Conclusion: The polyp MDT consensus management plan led to a change in the proposed management in almost half of the patients. This resulted in complete polypectomy for a large majority of patients referred to our service. Disclosure of interest: None Declared.